Key social determinants of the Russian large family - R. M. Sadykov; N. L. Bolshakova (Вестник университета)
The article presents a study of the state, dynamics, and social characteristics of large families in modern Russia. The authors analyse the social factors and features of having many children. The large families have undergone significant changes, have been greatly transformed in the process of social development and have a new social significance. Having many children is considered as the highest stage of family development and an indicator of a certain level of socio-economic development of society. It has been revealed that at the current stage of society’s development, quantitative indicators of the large families are decreasing in terms of the number of children, and childless marriages are becoming more widespread and popular. The key determinants and characteristics of the large families are identified such as the increase in their number, predominance of families with three and four children, spread of the large families depending on the region of residence. A negative trend persists which confirms the established pattern: with the birth of every next child, the family becomes low-income and less prosperous. In the large families, this pattern is confirmed: the number of poor family groups is increasing. It is determined that the amount of children affects family relationships, financial situation, and socio-psychological well-being. The focus on creating families with many children is considered a positive factor for the development of the family institution.